Acute Toxicity Study of an Herbal Hypolipidemic Preparation - Pradeep K Sharma; Yogendra Mavai; Suman Jain (Current Research in Pharmaceutical Sciences, 2013)
Medicinal plants have been used in various traditional systems, as they have potential against numerous diseases like cardiovascular disease. Currently, more than 200 clinically useful prescription drugs are derived from plants. Most of these were developed because of their use in traditional medicine. In several ancient systems of medicine including Ayurveda, Siddha and Unani, Achyranthus aspera and Murraya koenigii, two medicinally important herb from mainly Asian origin has vast number of therapeutic applications including hypolipidemic activity but very little information is available about their safety profile. It is a common believe that herbal products are safe because of which nobody care for the evaluation of their final preparation. We strongly recommend performing safety studies for the herbal preparations because all the extracts used are chemical in nature and there is strong possibility that these chemicals may react with each other and form some toxic compound or interact with the biomolecules. Keeping these things in mind, the present study has been envisaged and it was observed that water and chloroform extracts of Achyranthus aspera and Murraya koenigii are safe, based on the acute toxicity studies, as no abnormal changes are observed in treated animals. The combinations of both the extracts in 1:1 ratio are also safe and can be encapsulated into hard gelatin capsule of 000 size for human use.